The Relationship between Family Support and Diet Compliance in Hypertension Patients - Cindy Ratna Ardella; Abi Muhlisin (GLOBAL HEALTH SCIENCE GROUP, 2024)
Family support is one factor that cannot be ignored because it has a significant contribution and is a strengthening factor that influences patient dietary compliance hypertension. This research seeks to explore the relationship between family support and dietary adherence among individuals suffering from hypertension at the UPDT Gambirsari Health Centre. This study employs a quantitative research method featuring a correlational descriptive design, utilising a cross-sectional research approach. The research sample was a number of hypertension sufferers obtained from calculations using the Slovin formula (5%) and in accordance with the researchers' criteria, namely 87 respondents. Data collection was carried out using a questionnaire that measured the level of family support, namely with the results of the validity and reliability of the cronbach alpha results of 0.917 for 17 valid questions and hypertensive dietary adherence, namely with the results of the validity and reliability of the cronbach alpha value of 0.755 with 12 valid questions.. Bivariate analysis used the Spearman Rank correlation test. The results of collecting data on family support with the most categories, namely the sufficient family support category, were 54 respondents (62.1%), and the highest category of diet compliance was quite obedient, namely 49 respondents (56.3%). The research results showed a significant Spearman test of 0.05, the correlation between family support and hypertension diet compliance, obtained a probability number (p-value) = 0.001 (significant value for both variables 0.001<0.05), In other words, the null hypothesis (H0) was rejected. Thus, it can be concluded that this value indicates a relationship between family support and dietary compliance among hypertension sufferers at the Gambirsari Community Health Centre UPTD.